Proteoglycomics: Recent Progress and Future Challenges - Ly, Mellisa (Mary Ann Liebert, Inc., 2010)
Proteoglycomics is a systematic study of structure, expression, and function of proteoglycans, a posttranslationally modified subset of a proteome. Although relying on the established technologies of proteomics and glycomics, proteoglycomics research requires unique approaches for elucidating structure–function relationships of both proteoglycan components, glycosaminoglycan chain, and core protein. This review discusses our current understanding of structure and function of proteoglycans, major players in the development, normal physiology, and disease. A brief outline of the proteoglycomic sample preparation and analysis is provided along with examples of several recent proteoglycomic studies. Unique challenges in the characterization of glycosaminoglycan component of proteoglycans are discussed, with emphasis on the many analytical tools used and the types of information they provide.